Trends in sales of drugs for asthma in New Zealand, Australia, and the United Kingdom, 1975-81. Issue 6441 (11th August 1984) - Keating, G; Mitchell, E A; Jackson, R; Beaglehole, R; Rea, H
Abstract : As part of an investigation into the recent epidemic of deaths from asthma in New Zealand, trends in the sales of drugs for asthma in New Zealand, Australia, and the United Kingdom during 1975-81 were examined. Data on sales of drugs were obtained from an international pharmaceutical market research organisation. A striking increase in sales of sympathomimetic aerosols, steroid aerosols, and theophylline per caput occurred in all three countries, with the greatest increase occurring in New Zealand. Sales of sodium cromoglycate also increased in New Zealand and the UK but fell in Australia. By 1981 New Zealand had the highest sales of all these drugs per caput. Explanations for the rising mortality from asthma in New Zealand despite large increases in drug sales need to be explored. Although the temporal association between mortality and sales of drugs suggests that direct drug toxicity is unlikely, there may be more subtle adverse effects of drug use.